2015
DOI: 10.1007/s10753-015-0254-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administration of Amlodipine and Lacidipine on Inflammation-Induced Bone Loss in the Ovariectomized Rat

Abstract: This study was performed to evaluate the possible protective effect of two calcium channel blocker's "lacidipine (LAC) and amlodipine (AML)" on bone metabolism in an experimental ovariectomized and inflammation-induced osteoporosis rat model (OVXinf). For the purpose of this study, the rats were divided into eight groups, each containing eight rats: sham-operated control (group 1, SH), sham + inflammation (group 2, SHinf), ovariectomy (group 3, OVX), ovariectomy + inflammation (group 4, OVXinf), ovariectomy + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 89 publications
1
8
1
Order By: Relevance
“…Interestingly, these findings contradict previous studies investigating the effect amlodipine on bone metabolism and osteoporosis (Karakus et al, 2016;Ushijima et al, 2010). Ushijima et al (2010) postulated that amlodipine prevents a reduction in bone mineral density in stroke-prone spontaneously hypertensive rats through an inhibition of osteoclast activity.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, these findings contradict previous studies investigating the effect amlodipine on bone metabolism and osteoporosis (Karakus et al, 2016;Ushijima et al, 2010). Ushijima et al (2010) postulated that amlodipine prevents a reduction in bone mineral density in stroke-prone spontaneously hypertensive rats through an inhibition of osteoclast activity.…”
Section: Discussioncontrasting
confidence: 80%
“…Halici et al (2008) demonstrated that amlodipine protects against ovariectomyinduced bone loss. Furthermore, Karakus et al (2016) showed in an experimental ovariectomised and inflammation-induced osteoporosis rat model that amlodipine does not only prevent the ovariectomyand inflammation-induced loss of the osteogenic factors runt-related transcription factor 2 (Runx2) and type I collagen 1a1 (Col1a1) but even induces a 3-to 4-fold elevation of Runx2 and Col1a1 expression when compared to non-osteoporotic controls. Accordingly, the authors proposed that amlodipine may be used as a therapeutic agent for osteoporosis treatment in hypertensive patients (Karakus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that IL-17 production can occur independently of IL-23 stimulation [87] and that IL-1β is capable of driving maturation of IL-17 producing cells [88,89]. This supports a role for the IL-1 family in AS especially since IL-23 blockade is ineffective for spinal disease progression [90,91]. IL-1β is capable of inducing the expression of other inflammatory cytokines from CD4+ and CD8+ cells; this allows for an initiation of an inflammatory response seen in tissue repair.…”
Section: Il-17a and Other Il-17 Family Cytokines In Tissue Repairmentioning
confidence: 72%
“…Accordingly, the N/L-type CCB has a probability of less activation of the renin-angiotensin system [18]. Moreover, the administration of AML suppresses an inflammatory response by reducing the production of TNF-alpha, IL-1beta, and IL-6 [19], all of which are osteoclastogenic [20, 21]. Lin demonstrated that AML compared to the control group significantly increased the testosterone level in male SHR without affecting the levels of the follicle-stimulating and luteinizing hormone [21].…”
Section: Discussionmentioning
confidence: 99%